Indigeneity, culture and the UN Sustainable Development Goals / Dominic O'Sullivan. - O'Sullivan, Dominic, 1970- (Sustainable Development Goals series., 2023)
This volume examines the UN Sustainable Development Goals from an indigenous perspective and, specifically, with reference to the right to self-determination. It refers to the UN Declaration on the Rights of Indigenous Peoples and domestic instruments such as New Zealand's Tiriti o Waitangi to suggest how the goals could be revised to support self-determination as a more far-reaching and ambitious project than the goals imagine in their current form. It primarily draws its material from Australia, Canada, and New Zealand to support analysing the goals' policy relevance to wealthy states and the political claims that indigenous peoples make in established liberal democracies.